2009
DOI: 10.1016/j.cell.2009.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Components Contribute to Hypersensitive Cell Death in Arabidopsis

Abstract: Autophagy has been implicated as a prosurvival mechanism to restrict programmed cell death (PCD) associated with the pathogen-triggered hypersensi-tive response (HR) during plant innate immunity. This model is based on the observation that HR lesions spread in plants with reduced autophagy gene expression. Here, we examined receptor-mediated HR PCD responses in autophagy-deficient Arabidop-sis knockout mutants (atg), and show that infection-induced lesions are contained in atg mutants. We also provide evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
249
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(259 citation statements)
references
References 45 publications
7
249
0
3
Order By: Relevance
“…5 Many autophagy genes (Atg3, Atg5, Atg7, Atg9, and Atg16l1) are essential for normal mouse development since their deletion caused neonatal lethality. [45][46][47][48][49] Autophagy also induces cell death, in distinct organisms including mammals, [1][2][3][4][16][17][18][19][20] Drosophila, 50 Caenorhabditis elegans, 51 plants, 52 protists, 53 and yeast. 54 How autophagy plays a role in both a cell survival and cell death could be explained by the level of autophagic flux in cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 Many autophagy genes (Atg3, Atg5, Atg7, Atg9, and Atg16l1) are essential for normal mouse development since their deletion caused neonatal lethality. [45][46][47][48][49] Autophagy also induces cell death, in distinct organisms including mammals, [1][2][3][4][16][17][18][19][20] Drosophila, 50 Caenorhabditis elegans, 51 plants, 52 protists, 53 and yeast. 54 How autophagy plays a role in both a cell survival and cell death could be explained by the level of autophagic flux in cells.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] A variety of studies show membrane fusion to be important to the defense process that plants have toward pathogens as well as different types of defense responses. 9,11,[34][35][36][37][38][39][40][41][42] While the list of functions that the membrane fusion and vesicle transport proteins have is large, it is less clear whether the proteins also are engaged in other, but related functions.…”
Section: Introductionmentioning
confidence: 99%
“…The role autophagy in plant defence responses against invading pathogens is a matter of ongoing debate; however, existing evidence suggests its involvement (Liu et al 2005 ;Patel and DineshKumar 2008 ;Hofi us et al 2009 ;Yoshimoto et al 2009 ). For example, Patel and Dinesh-Kumar ( 2008 ) reported that autophagy-defi cient (antisense At-Atg6 ) A. thaliana plants underwent an uncontrolled hypersensitive response (HR) after infection with avirulent P. syringae pv.…”
Section: Autophagymentioning
confidence: 97%
“…Similar results were previously observed in tobacco plants defi cient in Nt-atg6/Beclin1 or Nt-atg7 (after VIGS) following infection with tobacco mosaic virus (Liu et al 2005 ) These fi ndings suggest that autophagy is a regulatory mechanism just before commitment stage for PCD that occurs during HR. However, the autophagy can also be a positive regulator of PCD during the HR as shown by infection of autophagy-defi cient A. thaliana knockout plants with avirulent Pto DC3000 ( AvrRpm1 ) did not lead to an uncontrolled HR lesion spread (Hofi us et al 2009 ). Yoshimoto and co-workers suggest that the differences between these studies may relate to differences in pathogen-treated plant or leaf age (Yoshimoto et al 2009 ).…”
Section: Autophagymentioning
confidence: 98%